Impacts of woody encroachment on the fate of soil CO₂ in grassland watersheds - Anhold, Christa Lee (Kansas State University, 2023)
Woody vegetation is encroaching into grasslands worldwide. Previous research has shown that woody encroachment impacts stream flow, nutrient concentrations, and suspended solid loads. However, little is known about deeper subsurface impacts, including impacts to groundwater residence time and composition. We examined these impacts at Konza Prairie Biological Station, a native tallgrass prairie in the Flint Hills of Kansas, USA. Previous research in the study area has found that groundwater CO₂ levels are rising, and we hypothesize that woody encroachment may be a driver. To help test this hypothesis, we compared groundwater chemistry and residence time between two watersheds, which differ in levels of woody encroachment (20% and 40%) as a result of differences in watershed burn frequency (1 yr vs 4 yr, respectively). Every three to four weeks during the 2022 water year, we collected groundwater and stream samples from each watershed and analyzed them for major ion chemistry. Geochemical modeling calculations indicate that an average of 4.4 mmol of CO₂ is added per liter of recharge in the more encroached watershed whereas 4.9 mmol of CO₂ is added per liter of recharge in the less encroached watershed. Groundwater residence time tracers, SF₆ and CFCs, collected at four times during the study period do not reveal clear differences between the watersheds. Groundwater residence time varied mostly as a function of the source of groundwater and the time of sample collection and thus do not appear to explain differences in CO₂ inputs between watersheds. Instead, we interpret that differences in CO₂ inputs reflect differences in the residence time of recharge water in the overlying soils. Woody encroachment alters soil root distributions, which in turn can increase soil hydraulic conductivity. If water passes through soils more quickly during recharge, kinetic reaction path modeling indicates that greater weathering occurs deeper in the subsurface rather than in the soil, which decreases the amount of dissolved inorganic carbon the groundwater can store, consistent with our measured groundwater chemistries. These findings suggest that woody encroachment is not driving the increase in groundwater CO₂ inputs over time but is instead causing differences in CO₂ levels between watersheds through its impact on soil hydraulic properties.
Keywords: Konza Prairie; Groundwater; Woody encroachment; Water quality; CO2